2013
DOI: 10.1080/19476337.2012.761651
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the alkaline and acid treatments on the physicochemical properties of corn starch

Abstract: Corn starches were isolated using three different methods: water steeping, alkaline steeping, and acid steeping. The effects on their structural, micro structural, thermal, and chemical properties were evaluated, with especial emphasis in the alkaline process that is close related to the nixtamalization process. The isolation method influences the amylose content, crystallinity, and enthalpy of the starch granules. Scanning electron microscopy showed that the isolation method produced changes on the surface of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 31 publications
(30 reference statements)
7
43
0
6
Order By: Relevance
“…The surfaces were corroded when starch was treated with acid and alkali. Rough surfaces indicated that both the amorphous and crystalline regions contributed to rough surfaces because both the amorphous and crystalline parts were hydrolyzed by the acid and alkali (Abdorreza et al 2012;Palacios-Fonseca et al 2013). PVA filled the spaces in the starch particles to a certain extent and covered the surfaces of the starch particles.…”
Section: Fig 3 X-ray Diffraction Patterns Of the Corn Starch And Trmentioning
confidence: 99%
See 1 more Smart Citation
“…The surfaces were corroded when starch was treated with acid and alkali. Rough surfaces indicated that both the amorphous and crystalline regions contributed to rough surfaces because both the amorphous and crystalline parts were hydrolyzed by the acid and alkali (Abdorreza et al 2012;Palacios-Fonseca et al 2013). PVA filled the spaces in the starch particles to a certain extent and covered the surfaces of the starch particles.…”
Section: Fig 3 X-ray Diffraction Patterns Of the Corn Starch And Trmentioning
confidence: 99%
“…Chemical reagents such as acid (Zuo et al 2013;Shi et al 2009), alkali (Palacios-Fonseca et al 2013;Uthumporn et al 2012) and enzymatic (Hu 2007) treatments are often used in modification of starch. Acid treatment has been applied for the hydrolysis of starch granules and to produce soluble starch for many years.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was suggested that the alkali treatment dissociated some of the double helices of starch granule and enabled it to be more vulnerable for enzymatic attack (Spier et al, ; Wang & Copeland, ). It was also reported that the starch isolated by alkaline steeping resulted in lower protein and lipid contents of starch (Palacios‐Fonseca et al, ).…”
Section: Resultsmentioning
confidence: 94%
“…Matheson and Welsh (1988) suggested steeping grains in 0.2M aqueous ammonia solution for 48 h, macerating the solid pellet in 0.2M acetic acid, and extracting starch with 0.1M sodium chloride and toluene. Palacios-Fonseca et al (2013) used 0.1% (w/v) NaOH for 18 h, as suggested by Wang and Wang (2001), with slight modifications. Palacios-Fonseca et al (2013) used 0.1% (w/v) NaOH for 18 h, as suggested by Wang and Wang (2001), with slight modifications.…”
Section: Resultsmentioning
confidence: 99%